Effects of Intermittent Versus Continuous Energy Intakes on Insulin Sensitivity and Metabolic Risk in Women with Overweight. Issue 1 (20th December 2018) - Hutchison, Amy T.; Liu, Bo; Wood, Rachel E.; Vincent, Andrew D.; Thompson, Campbell H.; O'Callaghan, Nathan J.; Wittert, Gary A.; Heilbronn, Leonie K.
Abstract : Objective: This study aimed to compare intermittent fasting (IF) versus continuous energy intakes at 100% or 70% of calculated energy requirements on insulin sensitivity, cardiometabolic risk, body weight, and composition. Methods: Women with overweight ( n = 88; 50 ± 1 years, BMI 32.3 ± 0.5 kg/m 2 ) were randomized to one of four diets (IF70, IF100, dietary restriction [DR70], or control) in a 2:2:2:1 ratio for 8 weeks. IF groups fasted for 24 hours after breakfast on three nonconsecutive days per week. All foods were provided and diets matched for macronutrient composition (35% fat, 15% protein, 50% carbohydrate). Insulin sensitivity by hyperinsulinemic‐euglycemic clamp, weight, body composition, and plasma markers were assessed following a "fed" day (12‐hour fast) and a 24‐hour fast (IF only). Results: IF70 displayed greater reductions in weight, fat mass, total‐ and low‐density lipoprotein cholesterol, and nonesterified fatty acids compared with DR70 and IF100 (all P ≤ 0.05). IF100 lost more weight and fat than control. However, fasting insulin was increased. There were no group differences in insulin sensitivity by clamp; however, a 24‐hour fast transiently reduced insulin sensitivity. Conclusions: When prescribed at matched energy restriction, IF reduced weight and fat mass and improved total and low‐density lipoprotein cholesterol more than DR. IF prescribed in energy balance did not improve health compared with other groups, despite modest weight loss.